FREQUENCY AND CHARACTERISATION OF PANCYTOPENIA IN MEGALOBLASTIC ANAEMIA - Khattak, Muhammad Bilal; Ismail, Mohammad; Marwat, Zahid Irfan; Khan, Faramoz (Journal of Ayub Medical College Abbottabad, 2012)
Background: A wide variety of clinical conditions, that primarily or secondarily affect the bonemarrow may present with pancytopenia, one of such conditions is megaloblastic anaemia. The purpose of this study was to determine the frequency and nature of pancytopenia in megaloblastic anaemia. Methods: This was a prospective, cross-sectional descriptive study conducted in Medical Units, Ayub Teaching Hospital, Abbottabad, Pakistan during July 2010-January 2011. Total 90 patients were included in this study. Data were collected including history, clinical examination, haemoglobin level, mean cell volume, bone marrow examination and peripheral smear examination. Results: Of total 90 patients, 54 were male and 36 were female. Mean age was 28±15.84 years. Common presenting features were weakness, fever and bleeding manifestations. Pancytopenia was present in 63 (70%) patients. Most common presenting feature related to anaemia was weakness (80%). Bleeding manifestations, related to low platelet count were found in 35 (39%) patients. Physical Examination findings were: pallor (100%), splenomegaly (33%), bleeding manifestations (25%), hepatomegaly (17%), and hepatosplenomegaly (19%). Mean peripheral blood findings of the study population included haemoglobin level (6.25 g/dL), total leukocyte count (2818.7/Î¼L), platelet count (44040/uL), and reticulocyte count (1.7%). Mean values for red cells indices included red blood cells count (2.6 million/uL), mean corpuscular volume (114.3 fL), mean corpuscular haemoglobin (27.3 Ïg) and mean corpuscular haemoglobin concentration (31.8 g/dL). Conclusions: In megaloblastic anaemia, pancytopenia is a common and important clinical and haematological problem. Patients should be properly investigated for pancytopenia and its causes because many of them are completely curable while others are manageable. This will help to reduce patients' suffering, improve quality of life and prolong survival. Keywords: Pancytopenia, megaloblastic anaemia, bone marrow aspiration, acute leukaemia, aplastic anaemia, hypersplenism